Gambaran Tingkat Pengetahuan Dan Sikap Ibu Tentang Trauma Gigi Permanen Pada Anak Usia 8-12 Tahun : Kajian pada Ibu dari Murid SD Nabawi Islamic School, Kota Jakarta Timur (Laporan Kasus) - Afifah Refiana Dewi; Jeddy Jeddy; Idham Tegar Badruzzaman (Fakultas Kedokteran Gigi Universitas Trisakti, 2021)
Background: Children's dental trauma mostly occurs in the maxillary anterior teeth, and falls, sports, traffic accidents, etc. can cause dental trauma. Generally speaking, children experience dental trauma when they are 8-12 years old. Therefore, dental trauma is a serious problem that often occurs in children and requires special attention from parents, especially mothers. Objective: To understand mother’s knowledge and attitudes towards children’s permanent tooth trauma Method: A descriptive observational cross-sectional design was adopted to conduct a survey of 70 respondents. The data was collected using a questionnaire, including 21 questions, tested validity and reliability. The research data is presented in the form of a frequency distribution table. Results: The adequate degree of mother's description of children's dental trauma knowledge was 75.7%, less than 15.7%, and less than 8,6%. In terms of attitude, 44.3% of the respondents hold a high attitude, and 55.7% of the respondents hold a low attitude. Conclusion: Most mothers have a high understanding of dental trauma, but there are still many mothers who have a low attitude towards dental trauma.